The Influence of Islamic Branding, Online Customer Reviews, and Tagline on Online Purchase Decisions on Shopee - Salpina, Parjah; Umuri, Khairil; Halim, Hendra; Sari, Nurma (EKOBIS SYARIAH, 2024)
This research aims to analyze the influence of Islamic branding, online customer reviews and tagline on online purchasing decisions at Shopee by students in Banda Aceh City. The data used is primary data obtained from questionnaires distributed to 160 respondents, students who use Shopee ecommerce in Banda Aceh City. This research used a quantitative approach. The sampling technique uses purposive sampling techniques and is determined by the Hair formula. Technical data analysis using multiple linear regression with the SPSS. The results of this study indicate that the variables of Islamic branding, online customer review, and tagline have a positive and significant effect on online purchasing decisions at Shopee. Simultaneous testing found that the variables of Islamic branding, online customer review, and tagline have an effect on online purchasing decisions at Shopee